Emphasizing group project-based learning elements in designing instructional material for univariate time series analysis and forecasting/ Mahayaudin M. Mansor - M. Mansor, Mahayaudin
Project Based Learning (PBL) is a systematic teaching method in which students learn by engaging in realworld problems and applying the essential time series knowledge and univariate modeling concepts learned to solve the problems. In addition to PBL, this contribution emphasizes the importance of working together in groups so that students can improve their social skills, critical thinking, and numeracy skills. This is important because analysts and statisticians generally enjoy working in silos. In addition, univariate time series modeling and model validation procedures can be complicated for many students. Hence, the proposed instrumental material is carefully developed, comprising comprehensive step-by-step tasks related to univariate time series analysis using RStudio. The proposed hands-on group assignment outlines instructions and 13 steps centered on the seven Group PBL (GPBL) elements of planning, fieldwork, implementation, presentation, assessment-reflection, collaboration, and effective communication. Planning involves discussing data searches, setting targets and timelines, and distributing tasks among team members. While fieldwork in GPBL refers to gathering and compiling data and resources, its implementation requires team members to execute the outlined tasks meticulously to avoid mistakes. Students are required to present their group work to an audience, and peers will provide formative feedback with instructor guidance for group reflection and improvement. The other advantages are the range of R programming commands for univariate times series modeling and forecasting, and the qualitative and quantitative diagnostic criteria for residual assumptions are given in Steps 1 to 13. To the best of my knowledge, no similar instrumental material has been produced. Besides patenting, the benefits of using the proposed instrumental material for students include more profound knowledge about the topic, higher-order thinking skills, collaborative learning skills, and real-life applications that have value for public products, including publication.